Peran Metode Cerita dalam Meningkatkan Pemahaman Konsep Bilangan pada Anak MI/SD - Sofiyah, Khotna; Efrillia Nasution, Audy; Hafiza, Nayla; Risky, Riri Luftia (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Mathematics is one of the subjects that plays an important role in elementary education, because it not only provides knowledge about numbers and calculations, but also trains logical thinking skills. This study aims to analyze the role of the story method in improving the understanding of number concepts in MI/SD children. The method used in this study is a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation of the mathematics learning process in the classroom. The results of the study indicate that the story method is effective in helping children understand the concept of numbers, because it can attract their attention, make it easier to visualize numbers through narratives, and create connections between mathematical concepts and everyday life. The use of the story method has a positive impact on increasing children’s learning motivation and ability to solve problems related to numbers. Based on these findings, the story method can be used as an alternative in teaching mathematics to improve students’ understanding.